2016
DOI: 10.4103/0970-9185.173325
|View full text |Cite
|
Sign up to set email alerts
|

Nitroglycerine, esmolol and dexmedetomidine for induced hypotension during functional endoscopic sinus surgery: A comparative evaluation

Abstract: Background and Aim:Induced hypotension limits intra-operative blood loss to provide better visibility of the surgical field and diminishes the incidence of major complications during functional endoscopic sinus surgery (FESS). We aimed at comparing nitroglycerine, esmolol and dexmedetomidine for inducing controlled hypotension in patients undergoing FESS.Material and Methods:One hundred and fifty American Society of Anesthesiologists physical status I or II adult patients undergoing FESS under general anesthes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
52
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(55 citation statements)
references
References 35 publications
3
52
0
Order By: Relevance
“…Kim et al [9] reported that a continuous infusion of dexmedetomidine provides a surgical field view and hemodynamic stability similar to that of the target-controlled infusion of remifentanil. In endoscopic sinus surgery, dexmedetomidine provided better hemodynamic stability and operative field visibility than nitroglycerin-induced hypotension [10]. …”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Kim et al [9] reported that a continuous infusion of dexmedetomidine provides a surgical field view and hemodynamic stability similar to that of the target-controlled infusion of remifentanil. In endoscopic sinus surgery, dexmedetomidine provided better hemodynamic stability and operative field visibility than nitroglycerin-induced hypotension [10]. …”
mentioning
confidence: 99%
“…As an adjuvant to general anesthesia, dexmedetomidine provides additional benefits of reducing the dose of inhalation agent and opioid analgesics [910], improving the quality of recovery, decreasing postoperative nausea and vomiting [911], and enhancing postoperative gastrointestinal motility [12]. Gupta et al [7] also show that dexmedetomidine infusion allows significant reductions in the amounts of isoflurane and intraoperative fentanyl required, while maintaining the targeted blood pressure.…”
mentioning
confidence: 99%
“…A total of 115 articles were retrieved from three databases After excluded duplicating, The remaining 75 articles were identi ed for further assessment. In the end, eight RCTs were included [8][9][10][11][12][13][14][15] .…”
Section: Resultsmentioning
confidence: 99%
“…Ulger et al [16] compared dexmedetomidine with nitroglycerine to achieve controlled hypotension in patients scheduled for middle ear surgery. The infusion rate of drugs was titrated to maintain a mean arterial pressure between 65 and 75 mmHg.…”
Section: Discussionmentioning
confidence: 99%